First records of seven species of mantis shrimp from India (Crustacea: Stomatopoda) - Ahyong, Shane T.; Kumar, Appukuttannair Biju (Zootaxa, 2018)
The Stomatopoda of India is comparatively well studied, with 79 species recorded to date. We herein report on a series of stomatopods collected by commercial fishing trawlers from localities on the southwest and southeastern coasts of India. The present series includes 17 species of stomatopods collected as trawl bycatch; seven are the first Indian records: Lysiosquillina lisa Ahyong & Randall, 2001, Odontodactylus cultrifer (White, 1951), O. japonicus (De Haan, 1844), Faughnia formosae Manning & Chan, 1997, Busquilla plantei Manning, 1978, Carinosquilla spinosa Ahyong & Naiyanetr, 2002, and Quollastria kapala Ahyong, 2001. Faughnia formosae is the first member of the superfamily Parasquilloidea to be recorded from India. We also show that Acanthosquilla dighaensis Ghosh, 1998, is a junior synonym of Bigelowina phalangium (Fabricius, 1798), described from Bombay but widespread in Indian waters.